Intellectual Property and the Growing Effects of the Digital Divide - Works of Digital Media Institutions in Algeria as a Model - Safi, Salah; Razal, Hakima (Journal of Legal Studies and Researches, 2025)
The global digital system has recently witnessed an accelerated revolution that touched the technologies of digital communication media. This made it difficult to protect intellectual works in their technical and legal scopes due to the large digital gap between developed and developing countries. This study comes to present the causes of the digital divide and ways to treat it with a study of the protection of works of digital media institutions in Algeria as a model.